2021
DOI: 10.1177/14779714211024678
|View full text |Cite
|
Sign up to set email alerts
|

E-learning experiences of adults during Covid-19 outbreak: The moderating effect of gender

Abstract: Covid-19 has brought surprises in the educational landscape. Educational institutions had to hurriedly migrate all teaching, learning and assessment activities to online platforms. Such was the case of adult learners who had signed on to the access course for entrance into the University of Ghana. This study sought to find out how the e-learning experiences of adult learners differed across gender as they studied English language, Logic and Mathematics online. From a quantitative analysis of the data, the onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…It is seen that the social presence levels of the students participating in the research in virtual environments do not differ according to gender. While McSporran and Young (2001) stated that gender is an important factor in distance education at the beginning of the 2000s and that women are disadvantaged in terms of access to technology, it can be stated that this disadvantage is no longer valid with the development of mobile technologies and the internet today (Kwapong, 2022;Mulyono). From the data obtained, it has been observed that the social presence levels of the students registered in the associate and undergraduate programs and the students enrolled in the graduate program differ according to their age and the type of program they are enrolled in.…”
Section: Methodsmentioning
confidence: 99%
“…It is seen that the social presence levels of the students participating in the research in virtual environments do not differ according to gender. While McSporran and Young (2001) stated that gender is an important factor in distance education at the beginning of the 2000s and that women are disadvantaged in terms of access to technology, it can be stated that this disadvantage is no longer valid with the development of mobile technologies and the internet today (Kwapong, 2022;Mulyono). From the data obtained, it has been observed that the social presence levels of the students registered in the associate and undergraduate programs and the students enrolled in the graduate program differ according to their age and the type of program they are enrolled in.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of remote learning during the pandemic have emphasised the relevance of the home environment ( Barrot et al, 2021 ; Baczek et al, 2021 ) and studies of adult students that predated the pandemic highlighted the importance of being able to escape distractions and responsibilities at home, with those lacking support finding this more difficult ( Kahu et al, 2014 ). Related to the home environment and family situations, research conducted during the pandemic highlighted that gender too may influence adult students’ satisfaction with online learning ( Kwapong, 2021 ). For example, due to a disproportionate burden of family responsibilities, women can find remote learning difficult to manage ( Stone & O'Shea, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Flexibility, accessibility, and not being limited by physical time and space make online learning an important means of bridging formal and informal learning and facilitating the realization of learners' vision of lifelong education [3]. This was especially pertinent during the lockdown period of the COVID-19 pandemic, with educational institutions in 194 countries closing down [4]; it has been proposed that online learning become an important alternative form of learning for higher education and vocational training [5][6][7]. In addition, digital technology serves not only as a tool for learning, but also as a cultural medium for sharing ideas, and it can help adult students develop critical thinking about topics such as climate change, inequality, political conflict, and other issues related to sustainable development [8].…”
Section: Introductionmentioning
confidence: 99%